Multifactorial Background for a Low Biological Response to Antiplatelet Agents Used in Stroke Prevention - Wiśniewski, Adam (Medicina (Kaunas, Lithuania), 2021)
Effective platelet inhibition is the main goal of the antiplatelet therapy recommended as a standard treatment in the secondary prevention of non-embolic ischemic stroke. Acetylsalicylic acid (aspirin) and clopidogrel are commonly used for this purpose worldwide. A low biological response to antiplatelet agents is a phenomenon that significantly reduces the therapeutic and protective properties of the therapy. The mechanisms leading to high on-treatment platelet reactivity are still unclear and remain multifactorial. The aim of the current review is to establish the background of resistance to antiplatelet agents commonly used in the secondary prevention of ischemic stroke and to explain the possible mechanisms. The most important factors influencing the incidence of a low biological response were demonstrated. The similarities and the differences in resistance to both drugs are emphasized, which may facilitate the selection of the appropriate antiplatelet agent in relation to specific clinical conditions and comorbidities. Despite the lack of indications for the routine assessment of platelet reactivity in stroke subjects, this should be performed in selected patients from the high-risk group. Increasing the detectability of low antiaggregant responders, in light of its negative impact on the prognosis and clinical outcomes, can contribute to a more individualized approach and modification of the antiplatelet therapy to maximize the therapeutic effect in the secondary prevention of stroke.